Analisis Konseptual dan Praktis Penerapan Al-Qawa’id Al-Fiqhiyyah Al-Iqtishadiyyah dalam Pengembangan Ekonomi Syariah Kontemporer - Rahmat, Rahmat Nur Ramdan; Bisri, Hasan; Rusyana, Ayi Yunus (Masoem University, 2025)
This study provides an in-depth analysis of the concepts and implementation of Al-Qawa’id Al-Fiqhiyyah Al-Iqtishadiyyah in the development of contemporary Islamic economics. The fiqh economic principles serve not only as a legal foundation but also as a strategic guideline to address modern economic challenges such as digitalization, globalization, and sustainability. The study reveals that while these principles exhibit flexibility in adapting to the dynamics of the era, their application is often hindered by a lack of practical guidelines and differing interpretations among Islamic economic practitioners. This research highlights the urgency of aligning fiqh principles with global market demands without compromising shariah values. Proposed solutions include integrating fiqh principles into Islamic economic regulations, developing technology-based practical guidelines, and enhancing fiqh economic literacy among practitioners. The findings demonstrate that the strategic application of fiqh principles can strengthen the competitiveness of Islamic economics while upholding Islamic ethical values amidst global changes.